Enhanced Imaging of Lithium Ion Battery Electrode Materials. Issue 1 (1st January 2017) - Biton, Moshiel; Yufit, Vladimir; Tariq, Farid; Kishimoto, Masashi; Brandon, Nigel
Abstract : In this study we present a novel method of lithium ion battery electrode sample preparation with a new type of epoxy impregnation, brominated (Br) epoxy, which is introduced here for the first time for this purpose and found suitable for focused ion beam scanning electron microscope (FIB-SEM) tomography. The Br epoxy improves image contrast, which enables higher FIB-SEM resolution (3D imaging), which is amongst the highest ever reported for composite LFP cathodes using FIB-SEM. In turn it means that the particles are well defined and the size distribution of each phase can be analyzed accurately from the complex 3D electrode microstructure using advanced quantification algorithms. The authors present for the first time a new methodology of contrast enhancement for 3D imaging, including novel advanced quantification, on a commercial Lithium Iron Phosphate (LFP) LiFePO4 cathode. The aim of this work is to improve the quality of the 3D imaging of challenging battery materials by developing methods to increase contrast between otherwise previously poorly differentiated phases. This is necessary to enable capture of the real geometry of electrode microstructures, which allows measurement of a wide range of microstructural properties such as pore/particle size distributions, surface area, tortuosity and porosity. These properties play vital roles in determining the performance of battery electrodes.